عوامل الاستقرار الاقتصادي في العراق وإمكانية تحقيقها وفق نظرية كينز مع إشارة إلى واقع الاستقرار الاقتصادي دوليا - الكعبي، مليحة جبار عبد; البياتي، قيس مهدي حسن (الجمعية العلمية للدراسات التربوية المستدامة, 2022)
يعد الاستقرار الاقتصادي أحد أهداف السياسة الاقتصادية العامة للدولة، والاستقرار الاقتصادي هو مصطلح مزدوج يتكون من عاملين هما (التشغيل الكامل والمستوى العام للأسعار)، ولذلك فأن الاستقرار الاقتصادي هنا يشمل بتعبير آخر تفادي عاملي (البطالة والتضخم). باعتبارهن أهم ما يؤثر على الاستقرار الاقتصادي في أي دولة، ويمكن من خلالهما معرفة أي بلد والحكم عليه كونه مستقر اقتصادياً أو لا، كما أن هناك مؤشرات أخرى بالطبع لكن ترتبط وتتداخل مع هذين المؤشرين والتي ركز كينز عليهما في نظرياته وتوجهاته الفكرية، وهي تصلح للتطبيق العملي في الدول التي تعاني من المشاكل الاقتصادية ومنها العراق. Economic stability is one of the objectives of the general economic policy of the state, and economic stability is a double term consisting of two factors (full employment and the general level of prices), and therefore economic stability here includes in other words the avoidance of two factors (unemployment and inflation). As they are the most important thing that affects the economic stability in any country, and through them it is possible to know any country and judge it as being economically stable or not, and there are other indicators, of course, but they are related and overlap with these two indicators, which Keynes focused on in his theories and intellectual orientations, and they are suitable for practical application in Countries that suffer from economic problems, including Iraq.
Keywords: الاستقرار الاقتصادي -- نظرية كينز -- التنمية المستدامة -- العراق -- الاتفاقيات الدولية